Pemetaan Sektor Produksi Dalam Pemulihan Pertumbuhan Ekonomi DIY - Nuralam, Nuralam (STAI Denpasar Bali, 2023)
Economic growth is influenced by many sectors, including the production sector. Where the production sector can be a benchmark for the economic progress of a region. The production sector is the sector that contributes most to economic growth. Therefore, problems in the production sector must be viewed as macroeconomic and long-term problems. Where the development of the ability to produce goods and services as a result of an increase in production factors, in general, is not always followed by an increase in the production of goods and services of the same magnitude. The increase in production potential is often greater than the actual increase in production. Thus economic development is slower than its potential. The aim of the research is to map the production sector in the context of regional economic recovery, where later in this analysis there will be a comparison of the growth conditions of the production sector in DIY before the Covid-19 pandemic with conditions during the Covid-19 pandemic (2019-2020 period). The results of research into the agricultural, fisheries and forestry business categories (primary sector) are the base or potential sectors in Kulon Progo, Bantul and Gunung Kidul Regencies, while Sleman Regency and Yogyakarta City are not the base sectors in the agricultural, fisheries and forestry business categories .